The role of some plant secondary compounds in decreasing obesity and obesity-related inflammation: A review. (Funded work) - SAMIAA JAMIL ABDULWAHID KURDI; YONG-MENG GOH; MAHDI EBRAHIMI; ZAILINA HASHIM (International Journal of Pharma and Bio Sciences, 2018)
Obesity occurs when the adipose tissue and adipose mass grow dramatically with the aid of two mechanisms, adipocyte hyperplasia and hypertrophy. Obesity is caused by several factors including diet, inadequate physical activity, dysregulation of the genes and adipocytokines involved in the lipid metabolism. Obesity is associated with many serious medical complications and increase the risk of hypertension, renal disease, type 2 diabetes, coronary heart disease and certain cancers. The expansion of adipose tissue produces numerous bioactive substances known as adipocytokines or adipokines. These substances may contribute to various metabolic diseases through altered glucose, lipid homeostasis and inflammatory responses. It has been documented that the plasma concentration of inflammatory mediators, such as interleukin-6 and tumor necrosis factor-α, is increased in obesity and type 2 diabetes. The primary targets for preventing and treating obesity are a reduction of the overall amount of body fat, prevention of extra fat accumulation and eradication of side effects associated with chemically formulated anti-obesity drugs.Various pharmacological approaches have been proposed for weight loss and/or minimizing weight regain. Of these, many researchers have focused on medicinal plants due to their anti-obesity properties. For example, polyphenols have anti-oxidative, anti-inflammatory and neuroprotective effects signifying the natural defense properties of plant-based foods. Antioxidants in polyphenols control inflammation and lipid metabolism. Polyphenols may also play a role in ameliorating obesity. Not with standing the publication of some excellent reviews on anti-obesity agents, the current paper recapitulates the mechanisms of some natural bioactive phytochemicals or plant secondary compounds. These compounds have been identified for their ability to prevent chronic disorders.